Crystal Reports 2008 [ the complete reference - Peck, George (New York : McGraw-Hill, 2008)
This is the number-one bestselling guide to crystal reports - completely updated for the latest release. Comprehensive and authoritative, this guide explains how to create and publish visually effective, high-fidelity reports with "Crystal Reports 2008". You will learn to use all of the new and improved features to access enterprise data, format it, and deliver it as actionable business intelligence. "Crystal Reports 2008: The Complete Reference" begins by covering general report design techniques that will apply to virtually everyone who uses the tool. The book then explains how to use crystal reports as an enterprise-level reporting solution, and offers developers solutions for integrating crystal reports into web and windows platforms
Includes index
Keywords: Business report writing -- Data processing; Seagate Crystal reports